2016
DOI: 10.3109/09273972.2016.1159232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Refractive Errors and Ocular Biometric Outcomes after Intravitreal Bevacizumab for Retinopathy of Prematurity

Abstract: The study showed no significant difference of SE between the groups. High myopia was only present among the treated infants either with IVB or laser. Infants who received laser treatment significantly had thicker lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Lee et al found that AL did not differ among different treatment groups. Gunay et al 34 reported that in children who receive anti-VEGF drug therapy, the AL might be related to the development of myopia and is not related to the ACD or LT. The Bevacizumab Eliminates the Angiogenic Threat for ROP (BEAT-ROP) believes that anti-VEGF drug treatment may facilitate the continuation of the local growth factor expression and signalling pathways, allowing the anterior segment to develop normally.…”
Section: Open Accessmentioning
confidence: 99%
“…Lee et al found that AL did not differ among different treatment groups. Gunay et al 34 reported that in children who receive anti-VEGF drug therapy, the AL might be related to the development of myopia and is not related to the ACD or LT. The Bevacizumab Eliminates the Angiogenic Threat for ROP (BEAT-ROP) believes that anti-VEGF drug treatment may facilitate the continuation of the local growth factor expression and signalling pathways, allowing the anterior segment to develop normally.…”
Section: Open Accessmentioning
confidence: 99%
“…Intravitreal injection of anti-vascular endothelial growth factor (VEGF) antibodies is an alternative to laser treatment in severe cases of ROP, such as aggressive posterior ROP (APROP), and ROP in zone 1 or posterior zone 2 [6]. Different from laser treatment, anti-VEGF antibody injection may allow maturation of the peripheral retina and anterior segment, and reports indicate better structural and visual outcomes (median VA of 0.3 log-MAR at around 2 years after treatment for type 1 ROP [7]) and a reduced incidence of myopia compared with laser [6,[8][9][10][11][12][13][14][15][16], though not all studies support these findings [17,18]. Anti-VEGF antibody therapy may require more than one treatment application, with reported retreatment rates ranging from 4 to 14% [6,9,11,12], though higher rates of 27% have also been reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…They are also in agreement with Harder et al 9 and other groups who have published similar retrospective studies that demonstrated a definite correlation between IVB therapy and a reduced prevalence of myopia. [6][7][8]10 Overall, in both zone 1 and 2 disease (Fig. 5B), IVB therapy was associated with a lower prevalence of myopia and high myopia compared with laser treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Most studies, including the BEAT-ROP trial, have demonstrated a reduced prevalence of myopia and high myopia among IVBtreated infants compared with laser-treated infants with type I ROP. [6][7][8][9][10][11] Gunay et al reported a significantly higher prevalence of high myopia in infants with zone 1 ROP vs zone 2 disease and an increase prevalence of high myopia in those treated with laser photocoagulation compared to the IVB treated group. 12 None of the previous studies examined the pattern of longitudinal refractive error development among infants with type 1 ROP treated with IVB.…”
Section: Introductionmentioning
confidence: 99%